Genetic diversity of TLR2, TLR4, and VDR loci and pulmonary tuberculosis in Moroccan patients - Arji, Naima; Busson, Marc; Iraqi, Ghali; Bourkadi, Jamal Eddine; Benjouad, Abdelaziz; Bouayad, Abdellatif; Mariaselvam, Christina; Salah, Sofiane; Fortier, Catherine; Amokrane, Kahina; Marzais, François; Boukouaci, Wahid; et al. (The Journal of Infection in Developing Countries, 2014)
Introduction: Toll-like receptors (TLRs) 2, 4, and the vitamin D receptor (VDR) are central components of the innate and adaptive immunity against Mycobacterium tuberculosis (Mtb). TLR2, TLR4, and VDR polymorphisms were previously associated with tuberculosis (TB) and were here investigated as candidates for pulmonary TB (PTB) susceptibility in a Moroccan population group. Methodology: Genomic DNA from 343 PTB patients and 203 healthy controls were analyzed for 12 single nucleotide polymorphisms (SNPs) located in TLR2, TLR4, and VDR genes using polymerase chain reaction-based restriction fragment length polymorphism and TaqMan SNP genotyping assays. Results: The TLR2 +597 CT genotype was associated with protection against PTB (corrected p [pc] = 0.04; odds ratio (OR) = 0.65; 95% confidence interval (CI) = 0.45 - 0.94), and the TLR4 +7263 C allele was significantly associated with PTB susceptibility (pc = 0.04; OR = 1.63; CI = 1.06 - 2.57). The VDR [f,b,a,T] haplotype was found to confer protection (pc < 0.00001; OR = 0.18; CI = 0.09 - 0.35), while the TLR2 [-16934T,+597C,+1349T] haplotype seemed to be at risk (p = 0.03; OR = 1.52; CI = 1.01 - 2.30), but statistical significance was not reached. Finally, cross-analysis between polymorphisms of the three studied genes revealed significant interaction between TLR2 +597 and TLR4 +4434 SNPs towards protection against PTB (pc = 0.036), suggesting that the functionally relevant TLR4 +4434 SNP may act synergistically with TLR2 SNPs. Conclusions: TLR2 and TLR4 interaction and a specific VDR haplotype influence protection against PTB in Moroccans patients.